Efficient Data Security for Mobile Instant Messenger - Putra Wanda; Huang J. Jie (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Instant Messenger (IM) becomes one of the most popular applications in mobile technology and communication. A lot of users around the world installed it for daily activities. Current IM found security lacks both in authentication and encryption matters. Various IM growing today still not apply an efficient method in authentication and encryption process, conventional security methods and client-server architecture system have to risk too many users for attacking server such as compromising, cracking password or PINs by Unauthorized people. Common IM services lack native encryption to protect information being transmitted over the public network and still used high computation in the mobile environment, this problem needs efficient security methods. Then, in public IM also found various messages with fake users, it occurs because public IM carry out the separate system in authentication and encryption process, strong authentication need to solve this issue in messenger environment. The tremendous growth of mobile IM user needs efficient and secure communication way. This paper proposes a new efficient method for securing message both in encryption and authentication within the end-to-end model. In this research, security method proposes new algorithms based on Elliptic Curve (EC) works in Peer to Peer (P2P) architecture than a conventional client-server model. The result shows this method produces efficient time in authentication and encryption process while applying in a mobile environment. Besides, it is compatible with the mobile phone which has a limitation of computation capabilities and resources.